Responsible lending and responsible borrowing – new challenges of Polish banks - Markowski, Wojciech (Publishing House of the Wrocław University of Economics, 2009)
The crisis on the financial markets, resulting, among others, from the crash of the mortgage market in the United States, as well as serious difficulties in the European banking sector that brought about important consequences to bank clients, including consumers, resulted in a renewed discussion of the scope of regulation on the market of retail financial services. The programme document prepared by the European Commission and entitled “Driving European recovery” [2009] identifies the need to conduct a series of reforms to overcome the crisis and stimulate an economic revival. One of the five main goals related to the responsible and credible operation of the financial markets consists of convincing European investors, consumers, small and midsize companies that their savings are safe. This aim consists of guaranteeing access to credit and to rights related financial products. Responsible lending and responsible borrowing represents the direction of work identified by the European Commission that is to support the achievement of the aforementioned goal. (fragment tekstu)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 59, s. 315-323